Sex Differences in Acute Relief of Abstinence-Induced Withdrawal and Negative Affect due to Nicotine Content in Cigarettes - Perkins, Kenneth A. (Nicotine Tob Res, 2015)
INTRODUCTION: Acute cigarette smoking may relieve withdrawal and negative affect due to tobacco abstinence to a greater extent in women versus men. Yet, the relative contribution of the cigarette’s nicotine content to this sex difference is not clear. METHODS: Non-quitting dependent adult smokers (N = 44; 21 males, 23 females) participated in 2 virtually identical sessions, each after abstaining overnight (CO < 10 ppm) and differing only in the nicotine content of the designated cigarette. While blind to brand markings, they consumed a total of 24 puffs in controlled fashion for 2hr in each session, either from a nicotine (Quest 1, 0.6mg) or denicotinized (Quest 3, 0.05mg) cigarette. Withdrawal symptoms were obtained before and after smoking, and negative affect was assessed after each period of cigarette exposure consisting of 6 puffs every 25min. RESULTS: Men and women did not differ in baseline withdrawal and negative affect due to overnight abstinence, but reductions in each symptom were significantly influenced by the interaction of sex × nicotine/denicotinized cigarette (both p < .05). In men, but not in women, each symptom was generally decreased more by the nicotine versus denicotinized cigarette, and the nicotine cigarette reduced each to a greater degree in men versus women. CONCLUSIONS: Sex differences in relief of abstinence-induced withdrawal and negative affect due to the nicotine content in cigarettes are consistent with prior research indicating that nicotine per se, compared to non-nicotine smoke stimuli, is less rewarding in women versus men.